D. UZNADZE`S THEORY AS A CONCEPTION OF PERSONALITY - Imedadze, I.V. (Modern Psychology, 2019)
General psychological theory by D.N. Uznadze installation addresses the fundamental methodological problems, covering major categories of psychology, consciousness, unconscious, behavior, personality. The theory is relevant for all kinds of activities on any level of philogenesis, ontogenesis and actualgenesis and aims to study universal mechanism determining behavior. It also presents the whole system of viewpoints concerning specific human activity, i.e. it implies the theory of personality by referring to such issues as structure of personality, motivation, personal development, psychopathology, mental health and changing personality via psychocorrective (psychotherapeutic) influence. The latter has not been sufficiently worked out and presents the vector of further development of the conception.
Keywords: Uznadze`s theory, personality, motivation, development, psychopathology, mental health, psychotherapy.